The CAGT motif functions as an initiator element during early transcription of the baculovirus transregulator ie-1. - Pullen, S S (1995)
The highly conserved tetranucleotide CAGT is located at the RNA start site of the transregulator gene ie-1 of Autographa californica nuclear polyhedrosis virus (AcMNPV). The presence of this motif within numerous baculovirus early promoters and its similarity to transcriptional initiators suggested a fundamental role in viral transcription regulation. To determine the function of the CAGT motif, site-specific mutations were introduced within the ie-1 promoter fused to a reporter gene within AcMNPV recombinants. In previous studies, deletion of the CAGT motif (nucleotides -1 to +3) and the adjacent downstream activating region (nucleotides +11 to +24) abolished ie-1 transcription. Here, we show that nucleotide replacements within the CAGT motif reduced steady-state levels of ie-1 RNAs from the proper start site (+1), both early and late in infection. These CAGT mutations caused comparable reductions in the yield of ie-1 runoff RNAs from in vitro transcription reactions using nuclear extracts from AcMNPV-infected cells; the CA dinucleotide was most sensitive to substitution. Thus, the CAGT motif affects the rate of ie-1 transcription. Deletions upstream and downstream from the ie-1 RNA start site demonstrated that nucleotides -6 to +11 encompassing the CAGT motif were sufficient for proper transcription in a TATA-independent manner. Nonetheless, additional regulatory elements, which included the ie-1 TATA element, the ie-1 downstream activating region, and a heterologous upstream activating region, stimulated transcription from the motif. Thus, by all criteria examined, the ie-1 CAGT motif functions as a transcriptional initiator by its capacity to determine the position of the RNA start site and to regulate the rate of transcription. These findings suggest that by stimulating early transcription through the recruitment of host factors, the CAGT initiator accelerates expression of viral genes, such as ie-1, that are critical to establishing a productive infection.